The Economics of BitCoin Price Formation - Pavel Ciaian; Miroslava Rajcaniova; d'Artis Kancs (Economics and Econometrics Research Institute (EERI), 2014)
This paper analyses the relationship between BitCoin price and supply-demand fundamentals of BitCoin, global macro-financial indicators and BitCoin's attractiveness for investors. Using daily data for the period 2009-2014 and applying time-series analytical mechanisms, we find that BitCoin market fundamentals and BitCoin's attractiveness for investors have a significant impact on BitCoin price. Our estimates do not support previous findings that the macro-financial developments are driving BitCoin price.
Keywords: E31; E42; G12; 330; BitCoin; exchange rate; supply-demand fundamentals; financial indicators; attractiveness